GARAP SUSUNAN TARI TRADISI SURAKARTA PADA TARI RETNA TAMTAMA - Nanuk Rahayu (Institut Seni Indonesia Surakarta, 2013)
The writer is also the creator of the dance Retna Tamtama and the process of creation wasbased on a broad background. The crystallization of the writerâ€™s experience in working on â€œSrikandhiSenopatiâ€ had a strong impact on her soul. After much reading and contemplation, her imaginationwas stimulated and enriched by the reality of life today and even by her own personal experiences.Encouraged by these strong feelings, ideas emerged which were then transformed into atheme. In order to visualize the final work, stages were set to be used as a guideline. This wasfollowed by a process of creative work which involved preparation, formulation, and interpretation,based on the concept of treatment that was to be applied to the content and form of the danceand reflected in the dance movements, the musical accompaniment, or gending beksan, the costume,and the properties. The final stage of the creative process was the performance itself. Theidealism of the creator in performing her work meant that the dancers had to present a highquality of performance.